Prosocial Behaviours in a Creative Arts Day Camp for Children With and Without Special Needs: A Mixed-Methods Study - Beer, Laura; Andrus, Mary; Jordan Hubchik, (Canadian Journal of Counselling and Psychotherapy, 2020)
There is a lack of research on the social benefits of creative arts therapies in summer day camp settings that are focused on children with special needs. Researchers in this study sought to address this gap by using a mixed-methods, concurrent embedded design that explored the prosocial potentials of using art therapy and music therapy to support school-aged children with and without special needs in a 2-week summer camp. A unique team approach—consisting of faculty, clinical supervisors, and art and music therapists in training—was used to collect, analyze, and interpret data. The aims of the camp and the research project focused on social interaction, engagement in activities, and emotional expression. Pretest and post-test evaluations revealed significant findings within the areas of task orientation (p < .001), assertiveness (p < .001), and peer social skills (p < .001). Qualitative data were collected in the form of camper statements, parent/caregiver statements, and student journals. Results indicated the effectiveness of a combined creative arts therapy model in helping children with special needs develop their prosocial skills.